NK cell education: Physiological and pathological influences - Rascle, Philippe; Woolley, Griffin; Jost, Stephanie; Manickam, Cordelia; Reeves, R. Keith (Frontiers in Immunology, 2023)
Natural killer (NK) cells represent a critical defense against viral infections and cancers. NK cells require integration of activating and inhibitory NK cell receptors to detect target cells and the balance of these NK cell inputs defines the global NK cell response. The sensitivity of the response is largely defined by interactions between self-major histocompatibility complex class I (MHC-I) molecules and specific inhibitory NK cell receptors, so-called NK cell education. Thus, NK cell education is a crucial process to generate tuned effector NK cell responses in different diseases. In this review, we discuss the relationship between NK cell education and physiologic factors (type of self-MHC-I, self-MHC-I allelic variants, variant of the self-MHC-I-binding peptides, cytokine effects and inhibitory KIR expression) underlying NK cell education profiles (effector function or metabolism). Additionally, we describe the broad-spectrum of effector educated NK cell functions on different pathologies (such as HIV-1, CMV and tumors, among others).